2015
DOI: 10.18269/jpmipa.v20i2.585
|View full text |Cite
|
Sign up to set email alerts
|

Pengembangan Petunjuk Praktikum Ipa Untuk Meningkatkan Kemampuan Berpikir Kritis Siswa SMP

Abstract: ABSTRAKPenelitian ini bertujuan mengembangkan petunjuk praktikum IPA yang valid dalam meningkatkan kemampuan berpikir kritis siswa SMP. Indikator kemampuan berpikir kritis siswa mencakup interprestasi, analisis, evaluasi dan inferensi. Penelitian ini merupakan penelitian Research and Development dengan metode Analysis, Design, Development, Implementation and Evaluation (ADDIE). Validasi ahli dilakukan dengan uji expert terkait dengan format, isi/materi, dan bahasa, sedangkan uji coba produk diberikan kepada 35… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
27

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 7 publications
1
27
0
27
Order By: Relevance
“…Critical thinking skills students include formulating the problem (inference), make a hypothesis (inference), collect data (interpretation), analyze the data (explanation), and make conclusions (evaluation). So also with previous research Wahyuni [7] reported that the IPA developed practical guidance already eligible for use in teaching in junior and can enhance students' critical thinking skills. Beck [8] argues that learning using the experimental method can enhance innovative teaching methods that can be applied by teachers.…”
Section: Character Attitude Of Students (Diligent and Be Careful)supporting
confidence: 73%
“…Critical thinking skills students include formulating the problem (inference), make a hypothesis (inference), collect data (interpretation), analyze the data (explanation), and make conclusions (evaluation). So also with previous research Wahyuni [7] reported that the IPA developed practical guidance already eligible for use in teaching in junior and can enhance students' critical thinking skills. Beck [8] argues that learning using the experimental method can enhance innovative teaching methods that can be applied by teachers.…”
Section: Character Attitude Of Students (Diligent and Be Careful)supporting
confidence: 73%
“…Several factors causing the low mathematics literacy of students according to Rusdi [21], are: 1) the teachers' knowledge about mathematical literacy was low, 2) the learning approach still did not related to the material with the context of students' daily lives, 3) the assessment instruments was far from the mathematical literacy, 4) realistic mathematics education approach ever developed by researchers in learning mathematics has not been combined with the concept of literacy yet. According to Whardhani and Rumiati [22] and Masduki, et al [23], the teaching materials used in schools were not enough to support the achievement of students' mathematical literacy yet.…”
Section: Review Of Literaturementioning
confidence: 99%
“…In this way, teaching materials can support student learning and increase success his. Teaching materials can be defined as breakdowns from a set of materials arranged in a manner systematically both written and unwritten creating an environment or atmosphere allows students to study [25].…”
Section: Review Of Literaturementioning
confidence: 99%
“…Dalam kegiatan belajar mengajar bahan ajar turut mendukung proses pembelajaran yang dapat berbentuk bahan ajar cetak maupun non cetak. Bahan ajar merupakan rangkaian materi pembelajaran yang disusun secara sistematis sehingga membantu pemahaman peserta didik [9].…”
Section: Bahan Ajarunclassified